EAES recommendations on methodology of innovation management in endoscopic surgery - Neugebauer, Edmund; Becker, Monika; Buess, Gerhard F.; Cuschieri, Alfred; Dauben, Hans-Peter; Fingerhut, Abe; Fuchs, Karl H.; Habermalz, Brigitte; Lantsberg, Leonid; Morino, Mario; Reiter-Theil, Stella; Soskuty, Gabriela; et al. (Surgical endoscopy and other interventional techniques, 2010)
Under the mandate of the European Association for Endoscopic Surgery (EAES) a guideline on methodology of innovation management in endoscopic surgery has been developed. The primary focus of this guideline is patient safety, efficacy, and effectiveness.
Gesehen am 12.05.2023